Perancangan Kelayakan Usaha Pendirian Cabang Offline Store Kedai Kopi Berlalu di Kota Bandung - Raisha Azhari Ghaniyyah Tanra; Sinta Aryan; Nanang Suryana (Peneliti.net, 2022)
Kedai Kopi Berlalu is a coffee shop that has been established in Bandung since 2020. With the unique value and concept, Kedai Kopi Berlalu has successfully entered the stage of positive business growth. But during their growth period, Kedai Kopi Berlalu experienced a decline revenue in October 2021 due to long waiting time. This long waiting time was caused by a decreased employee’s performance because the number of employees are no longer adequate to serve the high number of customers in September 2021. Then because there is a limited working space so it is impossible for Kedai Kopi Berlalu to add their employee, so this research was conducted to do a business feasibility planning to help the establishment process of Kedai Kopi Berlalu’s branch in Bandung to solve the problem. The business feasibility planning will be conducted with the help of market, technical, and financial planning, as well STP marketing strategy, 4P marketing mix, NPV, IRR, and PBP. Then based on the results of the study, it shows that the NPV value is Rp221.644.253, the IRR is 20,22%, and the PBP is 3,11 years, so it could be said that the investment is feasible to open Kedai Kopi Berlalu’s branch in Bandung.